Pengaruh Variasi Masa Simpan Tempe sebagai Bahan Dasar terhadap Yoghurt Probiotik - Adrian Azhari Pulungan; Dea Fahrum Nisa; Yuli Agustinah Munthe; Rizki Amelia Nasution (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
Tempeh is a traditional fermented soybean product rich in protein and has great potential as a raw material for functional foods, including probiotic yogurt. The use of tempeh as a yogurt base provides an alternative for consumers seeking plant-based dairy substitutes while increasing the value of local fermented products. This study aimed to evaluate the quality of probiotic yogurt made from tempeh fermented with lactic acid bacteria derived from Yakult based on lactic acid bacteria (LAB) count, pH value, and organoleptic characteristics. A laboratory experimental method was employed using three fermentation periods: 1 day (P1), 2 days (P2), and 3 days (P3). Product quality was assessed through the Total Plate Count (TPC) method for LAB enumeration, pH measurement using a calibrated pH meter, and organoleptic evaluation of color, aroma, taste, and texture. The results showed that all treatments produced yogurt with a pH ranging from 3.62 to 4.70, which is consistent with yogurt characteristics. The best treatment was P1, producing 8.72 × 10⁷ CFU/mL of LAB, meeting the Indonesian National Standard (SNI 2981:2009). Organoleptic evaluation indicated a yellowish-brown color, neutral aroma, thick texture, and slightly unsweetened taste. Therefore, tempeh has strong potential as an alternative substrate for producing high-quality probiotic yogurt.